Predicting Heat Stress to Inform Reef Management: NOAA Coral Reef Watch's 4-Month Coral Bleaching Outlook - Liu, Gang; Eakin, C. Mark; Chen, Mingyue; Kumar, Arun; De La Cour, Jacqueline L.; Heron, Scott F.; Geiger, Erick F.; Skirving, William J.; Tirak, Kyle V.; Strong, Alan E. (Frontiers in Marine Science, 2018)
The U.S. National Oceanic and Atmospheric Administration’s (NOAA) Coral Reef Watch (CRW) operates a global Four-Month Coral Bleaching Outlook system for shallow-water coral reefs in collaboration with NOAA’s National Centers for Environmental Prediction (NCEP). The Outlooks are generated by applying the algorithm used in CRW’s operational satellite coral bleaching heat stress monitoring, with slight modifications, to the sea surface temperature (SST) predictions from NCEP’s operational Climate Forecast System Version 2 (CFSv2). Once a week, the probability of heat stress capable of causing mass coral bleaching is predicted for four months in advance. Each day, CFSv2 generates an ensemble of 16 forecasts, with nine runs out to 45 days, three runs out to three months, and four runs out to nine months. This results in 28-112 ensemble members produced each week. A composite for each predicted week is derived from daily predictions within each ensemble member. The probability of each of four heat stress ranges (Watch and higher, Warning and higher, Alert Level 1 and higher, and Alert Level 2) is determined from all the available ensemble members for the week to form the weekly probabilistic Outlook. The probabilistic Four-Month Outlook is the highest weekly probability predicted among all the weekly Outlooks during a four-month period for each of the stress ranges. An initial qualitative skill analysis of the Outlooks for 2011-2015, compared with CRW’s satellite-based coral bleaching heat stress products, indicated the Outlook has performed well with high hit rates and low miss rates for most coral reef areas. Regions identified with high false alarm rates will guide future improvements. This Outlook system, as the first and only freely available global coral bleaching prediction system, has been providing critical early warning to marine resource managers, scientists, and decision makers around the world to guide management, protection, and monitoring of coral reefs since 2012. This has been especially valuable during the third global coral bleaching event that started in mid-2014 and extended into mid-2017. The Outlook system is an integrated component of CRW’s global decision support system for coral bleaching. Recent management actions taken in light of this system are discussed.